Simulating Systems Thinking under Bounded Rationality. (16th September 2020) - Sellers, Mark W.; Sayama, Hiroki; Pape, Andreas D.
Abstract : Brian Arthur's El Farol bar model of bounded rationality provides a simple computer model of decision making in a complex, dynamic, and self-organized environment. Can systems thinking provide a viable alternative strategy to traditional methods for dealing with these types of problems? Nine different agents, designed from both traditional and systems perspectives, compete in fifteen variants of the El Farol environment and their performance in 4 categories—Winner, Top Performers, Competitive, and Vulnerable—is compared. We show that systems thinking is a competitive strategy that is, at least, on par with traditional strategies and may be less vulnerable to elimination or ruin. However, there are two consequential elements that emerge. First, all strategies have some environments where they succeed and others where they fail. Second, as the population of practitioners adopts these adaptive, systems-based strategies, the environment exhibits new behaviors with a new set of unintended consequences.